Investigation On the Physical, Mechanical and Corrosion Behaviour of 316L Austenitic Stainless Steel Nitriding at Elevated Temperature - @Sinawat, Clement Welley (IRC, 2016)
One of the most effective and economical ways to enhance the mechanical properties and corrosion behaviour of Austenitic Stainless Steel 316L series is through gas nitriding. The objective of this project covers the study of microstructure analysis of Austenitic Stainless Steel 316L, the mechanical strength of the nitrided and unnitrided Austenitic Stainless Steel 316L and as well as the corrosion behaviour of nitrided and unnitrided Austenitic Stainless Steel 316L.